Hydrobiological assessment of two lakes of Jahangirnagar University campus, savar, Bangladesh (Bangladesh Journal of Botany, 2024)
The physicochemical and biological parameters of the water in two different lakes on the Jahangirnagar University campus were evaluated between December 2018 and August 2019. The chosen metrics were air and water temperature, Secchi depth, alkalinity, conductivity, pH, total dissolved solids (TDS), dissolved oxygen (DO), soluble reactive phosphate (SRP), soluble reactive silicate (SRS), nitrate-nitrogen (NO3-N) and phytoplankton density (PD). The correlation between all the matrics was done. 37 orders of phytoplankton from lake-1 and 35 orders of phytoplankton from lake-2 were found under 8 classes (Cyanophyceae, Chlorophyceae, Bacillariophyceae, Synurophyceae, Euglenophyceae, Cryptophyceae, Dinophyceae, and Xanthophyceae). According to the principal component Analysis (PCA), 53.8% variation was found among the classes. In addition, Monoraphidium, Oscillatoria, Cosmarium, Actinastrum, Trachlelomonas, Euglena, Pediastrum, Pinnularia, and Synedra were found to be dominant species. It examined the relationships between various environmental factors and dominant phytoplankton species in two lakes and found that the effects of the physicochemical parameters differ depending on the lake and dominant phytoplankton type. The study found negative correlations between various water quality parameters and phytoplankton taxa, suggesting an influence of environmental conditions on phytoplankton communities.Bangladesh J. Bot. 53(1): 159-171, 2024 (March)